Experimental Study of Pressure Deformation on Honeycomb Structures With Variations in Hexagonal Size Tested Static Study Of Pressure deformation Experiments On Beehive Structure With Hexagonal Size Variations Tested Static - Sudirman Lubis; Chandra A. Siregar; Irpansyah Siregar; Edi Sarman Hasibuan; Munawar A. Siregar; Wawan S. Damanik (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
Since ancient times, humans have tried to create new materials that are strong, rigid, lightweight and inexpensive. The honeycomb structure is a man-made material that has a honeycomb geometry to minimize the amount of material used, to achieve a minimum weight so that a light mass is obtained for the construction. This honeycomb structure is commonly used in aerospace applications, transportation, F1 racing and many other industries. In general, the purpose of this research is to determine the level of deformation, stress-strain that occurs in the honeycomb structure which is tested statically in compression. The honeycomb is made using aluminum material with a thickness of 0.4 mm and then formed with varying hexagonal sizes, namely 2 mm, 4 mm and 6 mm. This compression test is carried out using a Universal Testing Machine with 2 positions, namely horizontal and vertical. The specimen is pressed until it finds a broken point that is visible on the graph. The results obtained from this compressive test are in the form of deformation values and the maximum force acting on the specimen. From the results of the comparison of hexagonal size variations, it can be concluded that the larger the size of the honeycomb hexagon, the greater the deformation that occurs